Retinal and Optic Nerve Integrity Following Monocular Inactivation for the Treatment of Amblyopia - DiCostanzo, Nadia R.; Crowder, Nathan A.; Kamermans, Braden A.; Duffy, Kevin R. (Frontiers in Systems Neuroscience, 2020)
In animal models, monocular deprivation (MD) by lid closure mimics the effects of unilateral amblyopia in humans. Temporary inactivation of one or both eyes with intraocular administration of tetrodotoxin has recently been shown to promote recovery from the anatomical effects of MD at post-critical period ages when standard recovery strategies fail. In the current study, the retinae and optic nerves of animals subjected to 10 days of monocular retinal inactivation were assessed for pathological changes as a means of assessing the viability of this potential new amblyopia therapy. Retinal sections from both eyes were subjected to haematoxylin and eosin staining, and were then examined for cell density and soma size in the ganglion cell layer. Sections of optic nerve from each eye were examined for neurofilament protein, myelin, glial cell density, and glial fibrillary acidic protein. Our study revealed no evidence of gross histopathological abnormalities following inactivation for 10 days, nor was there evidence of degeneration of axons or loss of myelin in the optic nerve serving inactivated eyes. On all measurements, the inactivated eye was indistinguishable from the fellow eye, and both were comparable to normal controls. We confirmed that our inactivation protocol obliterated visually-evoked potentials for 10 consecutive days, but visual responses were restored to normal after the effects of inactivation wore off. Notwithstanding the critical need for further assessment of ocular and retinal health following inactivation, these results provide evidence that retinal inactivation as a treatment for amblyopia does not produce significant retinal damage or degeneration.